Exploring Physical Activity Awareness Among BMC Education Students, Kathmandu - Ghimire, Labanya Devi; Lamichhane, Shamila (Baneshwor Campus Journal of Academia, 2024)
Introduction: Physical activity is influenced by one’s knowledge of the benefits of physical activities as well as positive attitudes towards participation in such activities. Several studies have pointed out a decline in physical activity among adolescent and youths upon enrolling to university life with such decline being on a rising trend. Enhancing university youths’ knowledge on physical activities and fostering positive attitudes towards physical activities is crucial to promote healthy lifestyles, enhance their wellbeing and possibly also influence their study positively. Objective: The objective of this study is to assess the knowledge and attitudes regarding physical activity among Bachelor of Education students of Baneshwor Multiple Campus, Kathmandu, Nepal. Methods: A descriptive cross-sectional study was conducted using a self-administered semi-structured questionnaire collecting primary data from 142 1st to 4th year bachelor of education students. Descriptive statistics like frequency, percentage, mean and standard deviation were used in data analysis. Results: Mean age of study participants was 20.37 years (SD ± 2.36) with higher representation of females (68.31%) than that of males (31.69%). Over 90% students answered yes to five out of seven knowledge statements. The proportion of students responding yes to the remaining two statements was 89.44% and 78.17% respectively. Likewise, over 80% students agreed on six out of seven attitude statements. However, as many as 61% of students still believed that physical activity is injurious while 28.17% remained neutral and only 10.56% disagreed on it. Conclusion: This study showed that the majority of BEd students possessed fairly good knowledge and attitude towards physical activity. Yet, this study revealed some gaps in both knowledge and attitudes regarding physical activities warranting campus management to take necessary measures for improvement in future.